Would Bring Your Own Device (BYOD) be welcomed by undergraduate students to support their learning during fieldwork?. Issue 3 (3rd July 2018) - Welsh, Katharine E.; Mauchline, Alice L.; France, Derek; Powell, Victoria; Whalley, W. Brian; Park, Julian
ABSTRACT: This paper reports student perceptions of the benefits and challenges of Bring Your Own Device (BYOD) in a fieldwork context. Student perceptions from six field courses across two institutions have been gathered using questionnaires and focus groups. Whilst a number of studies have focused on BYOD in a classroom context, little research has been undertaken about BYOD in a fieldwork context. The key findings suggest that around one fifth of students were not willing to use their own device during fieldwork citing loss or damage as the main reason. This key challenge is different to that which are found in a classroom which generally focus on network security, connectivity etc. The findings also suggest that some students believe that BYOD can have a negative impact on group work. There is a misalignment here between student and practitioner thinking with previous literature which suggests that practitioners believe BYOD and smart devices can enhance group work. The one key challenge which is found regardless of learning environment is inequality between those who have a device and those who do not.